Sultan Abu’l Mafakhir Mahmud Abdul Qadir, Sultan Agung Banten I : Relasi Sultan Bagian Barat Pulau Jawa Dengan Kekhalifahan Utsmaniyyah (1596-1651) - Harto, Jemmy (Tarikh : Journal of Islamic History and Civilization, 2025)
Sultan Abul Mafakhir Mahmud Abdul Qadirrole as Sultan and Ulama was crucial in reforming the government system of the Banten Sultanate, and paving the way to the golden age of the Banten Sultanate, both in the fields of religion, economy, education, and military. He took full power in 1624 when he was 28 years old. Since 1638 he has received the legitimacy of the title of 'sultan' directly from Mecca, which is a representation of the Ottoman Caliphate. Not only as a ruler with the title of the first sultan in Banten, Abdul Qadir also recorded his name as the first Sultan in the Archipelago to be officially appointed by the Syarif of Mecca, as Sultan Agung Banten I. During his time there were two twin suns on the island of Java that were fighting for influence, namely Sultan Agung Banten and Sultan Agung Mataram. Even though Mataram wanted to unite the entire island of Java, it turned out that Banten never submitted to Mataram. Instead of Mataram conquering Banten, it was through the grandson of Sultan Abul Mafakhir Mahmud Abdul Qadir who was later known as Sultan Ageng Tirtayasa who formed a coalition with Prince Trunojoyo to stage a coup and defeat Mataram.